2013
DOI: 10.1155/2013/201208
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for Green Supply Chain Evaluation

Abstract: Green supply chain management (GSCM) has become a practical approach to develop environmental performance. Under strict regulations and stakeholder pressures, enterprises need to enhance and improve GSCM practices, which are influenced by both traditional and green factors. This study developed a causal evaluation model to guide selection of qualified suppliers by prioritizing various criteria and mapping causal relationships to find effective criteria to improve green supply chain. The aim of the case study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Kumar et al (2012) have revealed that a green supply chain is an essential tool for corporate profitability. In green supply chain evaluation modeling, Falatoonitoosi et al (2013) have addressed issues such as organizational performance, green organizational activities, green suppliers, environmental factors, and green logistics. While sustainable development affects the various components of main supply chain activities, Linton et al (2007) have proposed five modules, including product design, reduced waste, increased product lifecycle, product end-of-life, and recovery processes in the supply chain that strongly affect sustainability.…”
Section: Theoretical Foundations and Literaturementioning
confidence: 99%
“…Kumar et al (2012) have revealed that a green supply chain is an essential tool for corporate profitability. In green supply chain evaluation modeling, Falatoonitoosi et al (2013) have addressed issues such as organizational performance, green organizational activities, green suppliers, environmental factors, and green logistics. While sustainable development affects the various components of main supply chain activities, Linton et al (2007) have proposed five modules, including product design, reduced waste, increased product lifecycle, product end-of-life, and recovery processes in the supply chain that strongly affect sustainability.…”
Section: Theoretical Foundations and Literaturementioning
confidence: 99%
“…Green supplier selection problem is a sort of complex multiple criteria decision making problem including both quantitative and qualitative factors, which may be inconsistent and uncertain. Due to the nature of supplier selection, MCDM methods are required to handle and solve the problem effectively [60]. Multiple criteria decision making (MCDM) using the decision making trial and evaluation laboratory (DEMATEL) was proposed in this case analysis.…”
Section: Case Analysis Methodsmentioning
confidence: 99%
“…For testing the model, as same as our previous research attempt [60], "case study with expert interview technique" is applied for this research. The objects were 10 professional experts who are working in supply chain departments of Iran Khodro Co. Each interview has been done individually by each expert and took time between minimum 30 minutes to maximum 45 minutes for each of them.…”
Section: Application and Testing Of The Modelmentioning
confidence: 99%
“…The green supply chain management is one of the important ways to improve the environmental performance, and the development of green supply chain depends on the realization of green supply chain coordination [39]. To promote the further development of green supply chains, increasing numbers of studies are inclined to design a reasonable coordination mechanism and an incentive mechanism to realize green supply chain coordination and to maintain the benefits of supply chain members [40].…”
Section: Green Supply Chain Coordinationmentioning
confidence: 99%